2019
DOI: 10.1038/s41598-019-51642-7
|View full text |Cite
|
Sign up to set email alerts
|

Ag-AgCl Nanoparticles Fixation on Electrospun PVA Fibres: Technological Concept and Progress

Abstract: Polymer-metal based material with unique 3D structure is an attractive substrate for the development of biomedical applications. A novel preparation of the composite from polymer fibres and silver nanoparticles has been designed through: (1) preparation of silver nanoparticles by phytosynthesis and (2) incorporation of these nanoparticles in a fibrous membrane prepared by electrospinning. The nanoparticle biosynthesis was performed in a pure environmental-friendly, easy, static, bottom-up in vitro regime using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
(26 reference statements)
2
10
0
Order By: Relevance
“…This is likely attributable to the completion of the synthesis process, and the formation of biogenic AgCl-NPs [11]. It was previously reported that P. vulgaris contains alkaloids, tannins, flavonoids, and phenolic compounds [29] that could be responsible for the bioreduction of Ag(I) ions into AgCl-NPs as well as their capping in the solution [30]. The green synthesis mechanism of AgCl-NPs is not clear yet, but it seems that secondary metabolites of P. vulgaris played an important role in their formation and stabilization.…”
Section: Visual Confirmation Of Green Synthesis Of Agcl-npsmentioning
confidence: 99%
“…This is likely attributable to the completion of the synthesis process, and the formation of biogenic AgCl-NPs [11]. It was previously reported that P. vulgaris contains alkaloids, tannins, flavonoids, and phenolic compounds [29] that could be responsible for the bioreduction of Ag(I) ions into AgCl-NPs as well as their capping in the solution [30]. The green synthesis mechanism of AgCl-NPs is not clear yet, but it seems that secondary metabolites of P. vulgaris played an important role in their formation and stabilization.…”
Section: Visual Confirmation Of Green Synthesis Of Agcl-npsmentioning
confidence: 99%
“…Vilamova Z. et al. have also observed this behavior [ 12 ]. Generally, increasing the applied voltage leads to a stable Taylor cone, and the columbic repulsive forces within the spinning jet force the viscoelastic solution to extend.…”
Section: Resultsmentioning
confidence: 76%
“…To add an antimicrobial agent to PVA, Vilamova Z. et al. have prepared a composite from silver nanoparticles encapsulated inside electrospun PVA nanofibers [ 12 ]. For this study, we aimed to find the best electrospinning parameters (including capillary–collector distance, voltage, and flow rate) for the newly prepared material graft urethanized poly(vinyl alcohol) (U-PVA) and comparing the results of fiber morphology, wettability and drug release rates between pure PVA and graft U-PVA specimens for pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The crystalline nature of the prepared Ag-AgCl NPs was confirmed by selected-area electron diffraction (SAED) patterns, and the crystal twinning typical in silver crystals was also apparent. In our previous study, 38 we used L1 to synthesize Ag NPs for p-nitrophenol decomposition. The Ag-AgCl NPs' core diameter was 14 ± 9 nm, and this correlates with these study results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%